RISK OF CEREBRAL MICROBLEEDS AND ICH IN STROKE ISCHEMIC AND TIA PATIENTS ASSOCIATED WITH THE USE OF ANTIPLATELET MEDICATIONS: A SYSTEMATIC REVIEW - Shafira Zulkarnain, Farah; Riyan Ashori Hidayat , Andhira (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Stroke is conventionally described as a neurological dysfunction linked with acute focal central nervous system (CNS) injury resulting from vascular sources. Ischemic stroke is a neurological impairment resulting from arterial blockage. Ischemic strokes are the most prevalent type of stroke. Antiplatelet therapy is essential to the treatment of noncardioembolic ischemic stroke and transient ischemic attack (TIA) in order to alleviate the severity of this burden. The evidence supports aspirin, aspirin-dipyridamole, clopidogrel, and ticagrelor, four antiplatelet medicines. These antiplatelets were selected as the most effective since they have been the subject of decisive clinical trials and are the most frequently referenced in clinical practice guidelines. The low incidence of intracranial hemorrhage (ICH) could be attributed to the fact that the majority of patients took aspirin instead of oral anticoagulants. The incidence of ICH was equivalent to that seen in trials that included antiplatelet drug participants. The study was unable to rule out the potential that the presence of microbleeds in patients on oral anticoagulants suggests an increased risk of ICH. The use of antiplatelet medicines enhanced the risk of strictly lobar MBs and the rate of intracerebral hemorrhage in CMB patients.